Effects of environmental factors on dimethylated sulfur compounds and their potential role in the antioxidant system of the coral holobiont. (7th April 2014) - Deschaseaux, E. S. M.; Jones, G. B.; Deseo, M. A.; Shepherd, K. M.; Kiene, R. P.; Swan, H. B.; Harrison, P. L.; Eyre, B. D.
Abstract : Biogenic dimethylsulfide (DMS) and its main precursors, dimethylsulfoniopropionate (DMSP) and dimethylsulfoxide (DMSO), are potential scavengers of reactive oxygen species in marine algae, and these dimethylated sulfur compounds (DSC) could take part in the algal antioxidant system. In this study, a link between the DSC production and the antioxidant capacity (AOC) of Acropora aspera reef coral was investigated under a range of environmental factors (temperature, light, salinity, and air exposure) that can lead to oxidative stress in the coral holobiont. Enhanced DMS(P)(O) production occurred under experimental conditions, indicating that DSC are potential biomarkers of stress level in coral tissue. Differences in concentrations and partitioning as a response to different treatments suggest that DSC production and turnover undergo different biochemical pathways depending on the type and severity of environmental stress. Osmotic pressure and light depletion led to an up‐regulation of the coral AOC that was correlated with a significant increase in DMSO : DSC ratio. These results, combined with a positive correlation between the AOC and DMSO concentrations under these two treatments, suggest that the DMSP‐based antioxidant system is involved in the overall antioxidant regulation of the coral holobiont. Enhanced DMS production coupled with an increased DMS : DSC ratio under increased temperature indicated that thermal stress triggers DMS formation in coral tissue. Considering the role that DMS can have in both climate regulation and the DMSP‐based antioxidant system, our findings highlight the need to further examine the fate of DSC in coral reef environments under scenarios of increasing sea surface temperatures.